Synthesis and molecular characterization of acrylate liquid crystalline resin monomers (ALCRM) - He, X P; Cai, W; Guo, L; Zhou, L Z; Nie, M H (Cellular and Molecular Biology, 2015)
A novel biocompatible resin monomer 4-3-(acryloyloxy)-2-hydroxypropoxy) phenyl 4-(3-(acryloyloxy)-2-hydroxypropoxy) benzoate, as an oral restorative - acrylate liquid crystalline resin monomer (ALCRM) was synthesized. The intermediate product and the final product were characterized by differential scanning calorimetry (DSC), polarized optical microscope (POM), and nuclear magnetic resonance (NMR). A resin matrix which has a potential application in dental composites was prepared by photopolymerizing ALCRM and triethylene glycol dimethacrylate (TEGDMA) as a primary and diluted monomer with a photosensitizer of camphorquinone (CQ) and 2-(Dimethylamino)ethyl methacrylate (DMAEMA) mixture. The molar ratio of ALCRM and TEGDMA was 7:3. The properties such as the curing depth, curing time, and the volumetric shrinkage of the resin matrix were investigated and compared with a traditional composite resin matrix Bis-GMA. After photocuring polymerization, the conversion degree of the resin matrix is 68.06%, higher than Bis-GMA/TEGDMA; the curing time is 4.08±0.20min, the curing depth is 2.10±0.17mm, and the volumetric shrinkage is 3.62%±0.26%. All the properties exhibit a better performance of the prepared resin matrix than Bis-GMA.